PROGRAM BIJAK LINGKUNGAN (BILING) BERBASIS PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN ECOLITERACY ANAK-ANAK PADA KOMUNITAS LARE SINAU BANYUWANGI - Amaliyah, Khofifah Indah; Hilmi, Muhammad Irfan; Hasan, Fuad (Comm-Edu (Community Education Journal), 2025)
The current problem is the low environmental awareness and ecoliteracy in children. The low awareness of children about the importance of caring behavior towards the environment is due to the absence of serious action from several parties to minimize this problem. This study aims to describe the implementation of the Environmental Wise Program (BILING) based on Project Learning to improve children's eco-literacy skills in the Lare Sinau Banyuwangi Community. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the BILING Program based on Project Learning is carried out through six stages including big questions, project design, schedule preparation, progress monitoring, outcome assessment, and experience evaluation. This program effectively encourages children to think critically and actively with a contextual and fun learning approach. The facilitator acts as a companion and guide. Parental participation and the Participatory Rural Appraisal approach increase children's sense of ownership and self-confidence. Children show increased eco-literacy skills in environmental understanding, caring attitudes, and sustainable practices. The BILING Program, which is based on project-based Learning, has a positive impact through a holistic and participatory approach.Keywords: BILING Program, Project Based Learning, Ecoliteracy Ability.